The Impact of Financial Literacy, Financial Digitalization, and Lifestyle on Financial Inclusion Through Technological Capital Among Student of State University of Surabaya - Benita, Almas; Susanti; Listiadi, Agung (Jurnal Pendidikan Edutama, 2025)
This study aims to analyze the influence of financial literacy, financial digitalization, and lifestyle on financial inclusion through technological capital among students of the Faculty of Economics and Business at Universitas Negeri Surabaya. The research employed a quantitative methodwith a survey approach, involving 250 respondents selected through purposive sampling. Data were analyzed using SEM-PLS. The finding sreveal that financial literacy has a positive influence on technological capital (p = 0.108), while financial digitalization shows a significant influence(p=0.000). Lifestyle also contributes positively to technological capital (p=0.000). Financial literacy have a direct effect on financial inclusion (p = 0.041), financial digitalization (p = 0.000) and lifestyle (p=0.000) show a positive influence. Technological capital significantly mediates the influence of financial literacy and financial digitalization on financial inclusion. These findings highlight the importance of integrating financial literacy and technological competence to support financial inclusion among college students.